JĀZEPS VĪTOLS AND THE TRADITION OF LATVIAN SONG FESTIVALS (Mūzikas akadēmijas raksti, 2024)
Between the last decades of the 19th century and until the end of World War II, Jāzeps Vītols was the most active, influential and brilliant figure in Latvia’s culture of music. Over the course of several decades, his work personified the first golden age of Latvian music, and the quintessence of Latvian musical culture was the Song Festival.The growth of Latvian choirs during the latter half of the 19th century was very rapid and dynamic. Choral singing brought along efforts which did not relate to music, ever more clearly making out the nation’s desire for consolidation and self-determination. This created a social and cultural phenomenon – the Song Festival. The first All-Latvian Song Festival took place in Riga, in 1973, it centered on a cappella choir singing, the national repertoire, and the participation of a broad range of professional musicians and amateur singers.Vītols played a particular role in the emergence of the Latvian Song Festivals, as one of the fathers of the national school of composition,  and as an ourstanding public activist and individual.